2022
DOI: 10.1007/s11912-021-01151-6
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumour DNA in Melanoma—Clinic Ready?

Abstract: Purpose of Review Liquid biopsies, including circulating tumour DNA (ctDNA), can inform a variety of clinical questions. This review examines the potential role of ctDNA as a clinical tool to inform clinical decision-making from early to late stage cutaneous melanoma. Recent Findings In pre-clinical studies, ctDNA has been shown to detect minimal residual disease and molecular relapse; predict and monitor response to therapy; and identify key resistance me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 72 publications
0
10
0
1
Order By: Relevance
“… 47 In a wider clinical context, ctDNA monitoring has the potential to become a commonly used tool to guide clinical decision-making in all melanoma patients, and future trials should include translational sub-studies to investigate the utility of this. 52 TebeMRD (NCT05315258) aims to establish whether treating uveal and CM patients who develop molecular relapsed disease after definitive treatment (assessed via serial measurements of ctDNA), can prevent or delay the appearance of macroscopic disease.…”
Section: Discussionmentioning
confidence: 99%
“… 47 In a wider clinical context, ctDNA monitoring has the potential to become a commonly used tool to guide clinical decision-making in all melanoma patients, and future trials should include translational sub-studies to investigate the utility of this. 52 TebeMRD (NCT05315258) aims to establish whether treating uveal and CM patients who develop molecular relapsed disease after definitive treatment (assessed via serial measurements of ctDNA), can prevent or delay the appearance of macroscopic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal analysis of ctDNA, as measured by ddPCR, was found to be predictive of disease relapse and response to adjuvant treatment in the absence of radiological findings in melanoma ( 9 , 19 ). Similarly, ctDNA monitoring of melanoma-associated somatic alterations was shown in a cohort of patients to predict disease progression ahead of radiological findings ( 10 ). Of note, the majority of the published studies in melanoma have used single mutation or limited targeted panel sequencing for ctDNA analysis ( BRAF , NRAS , KIT , and TERT ) ( 16 , 20 , 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple platforms have been developed to analyze ctDNA in different cancers including single mutation detection by dropletdigital PCR (ddPCR), next-generation sequencing (NGS), or whole-exome sequencing (WES), which have been reviewed previously (7,8). Existing evidence on the clinical utility of ctDNA testing in melanoma has emerged recently in retrospective and prospective studies (9,10). The use of personalized and tumor-informed ctDNA testing has been shown in several studies to detect molecular residual disease (MRD), and serve as an important prognostic tool to predict relapse in colorectal, breast, lung and urothelial cancers (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Although this study is only an initial glimpse into the potential of ctDNA to impact on clinical practice, it seems likely that noninvasive disease assessment will have a major role in oncology moving into the future. Many studies across tumor types have now demonstrated ctDNA as a marker of tumor burden and cancer proliferation 2,3 . In addition, ctDNA has been shown to be predictive of treatment response across a variety of treatment modalities 4–7 .…”
Section: Trial Name Main Hypothesis Phase Nct Nomentioning
confidence: 99%
“…Many studies across tumor types have now demonstrated ctDNA as a marker of tumor burden and cancer proliferation. 2,3 In addition, ctDNA has been shown to be predictive of treatment response across a variety of treatment modalities. [4][5][6][7] In adjuvant bladder cancer, reanalysis of an originally reported negative phase 3 trial suggests that ctDNA is highly predictive of benefit for atezolizumab versus observation.…”
Section: Potential Of Circulating Tumor Dna To Refine Immunotherapymentioning
confidence: 99%